Assessing the risk of heart failure in patients with diabetic retinopathy with type 2 diabetes mellitus - Sharma, Praful; Priyadarshi, B. P.; Singh, M. P. (International Journal of Advances in Medicine, 2025)
Background: Type 2 diabetes mellitus (T2DM) is associated with both microvascular and macrovascular complications, notably diabetic retinopathy (DR) and heart failure (HF), respectively. While DR is a well-established marker of retinal microangiopathy, emerging evidence suggests it may also reflect systemic vascular pathology. However, data on this association in the Indian population remains limited. Methods: A hospital-based cross-sectional observational study was conducted at GSVMMC, Kanpur, between August 2023 and February 2025. Ninety-two adults with T2DM were enrolled and assessed for DR using fundoscopic examination and graded from 0 to 3. Heart failure was diagnosed and classified via echocardiography into HFpEF, HFmrEF, and HFrEF. Biochemical markers, including HbA1c and NT-proBNP, were evaluated. Statistical analysis included Chi-square tests and ANOVA using statistical package for the social sciences (SPSS) v20. Results: Among the 92 patients, 73 (79.34%) had some form of heart failure, and 74 (80.43%) had DR. A significant association was found between DR and HF (p=0.001). The prevalence of HFrEF increased with DR severity from 10% in grade 0 to 35% in grade 3 DR (p=0.045). Additionally, poor glycemic control and higher body mass index (BMI) were common in patients with more severe DR and HF. Conclusion: DR is significantly associated with both the presence and severity of HF in T2DM patients. Retinal examination may serve as a practical, non-invasive tool for early cardiovascular risk stratification. These findings support integrated screening strategies in diabetic care.